Room temperature long-range coherent exciton polariton condensate flow in lead halide perovskites - Su, Rui (2019)
Novel technological applications significantly favor alternatives to electrons toward constructing low power–consuming, high-speed all-optical integrated optoelectronic devices. Polariton condensates, exhibiting high-speed coherent propagation and spin-based behavior, attract considerable interest for implementing the basic elements of integrated optoelectronic devices: switching, transport, and logic. However, the implementation of this coherent polariton condensate flow is typically limited to cryogenic temperatures, constrained by small exciton binding energy in most semiconductor microcavities. Here, we demonstrate the capability of long-range nonresonantly excited polariton condensate flow at room temperature in a one-dimensional all-inorganic cesium lead bromide (CsPbBr3) perovskite microwire microcavity. The polariton condensate exhibits high-speed propagation over macroscopic distances of 60 μm while still preserving the long-range off-diagonal order. Our findings pave the way for using coherent polariton condensate flow for all-optical integrated logic circuits and polaritonic devices operating at room temperature.